FTIR and Moisture Absorption of Yam Bean Starch Biocomposites with Yam Bean (Pachyrhizus erosus) Bagasse Fibers as Reinforcement - Mahardika, Melbi; Abral, Hairul; Kasim, Anwar; Arief, Syukri; Asrofi, Mochamad (Jurnal ILMU DASAR, 2018)
Biocomposites from yam bean starch with yam bean bagasse (YBB) fibers as reinforcement has been successfully fabricated. The fabrication method was solution casting. YBB was variated for 1, 2, 3 and 4wt% (from dry weight starch basis). 2 mL glycerol was used as a plasticizer. The relative humidity (RH) condition in moisture testing was 99%. The result shows that the addition YBB able to decreased moisture absorption of starch film. The lowest moisture absorption was in biocomposites with 4wt% YBB. The moisture absorption test was supported byfourier transform infrared (FTIR) data.Keywords: Biocomposite, yam bean, yam bean bagasse, moisture, FTIR